PROSPECTS FOR THE DEVELOPMENT OF FUNDRAISING ACTIVITIES IN UKRAINE - Гуменюк, Алла; Гарматюк, Олена (SWorldJournal, 2023)
The purpose of writing the article is to study the concept of «fundraising» and its main tools. The experience of using fundraising tools in non-profit public organizations was studied. Fundraising activities, which at the all-Ukrainian and international